Potential reductions in ambient NO2 concentrations from meeting diesel vehicle emissions standards. (8th November 2017) - von Schneidemesser, Erika; Kuik, Friderike; Mar, Kathleen A; Butler, Tim
Abstract: Exceedances of the concentration limit value for ambient nitrogen dioxide (NO2 ) at roadside sites are an issue in many cities throughout Europe. This is linked to the emissions of light duty diesel vehicles which have on-road emissions that are far greater than the regulatory standards. These exceedances have substantial implications for human health and economic loss. This study explores the possible gains in ambient air quality if light duty diesel vehicles were able to meet the regulatory standards (including both emissions standards from Europe and the United States). We use two independent methods: a measurement-based and a model-based method. The city of Berlin is used as a case study. The measurement-based method used data from 16 monitoring stations throughout the city of Berlin to estimate annual average reductions in roadside NO2 of 9.0 to 23 µg m −3 and in urban background NO2 concentrations of 1.2 to 2.7 µg m −3 . These ranges account for differences in fleet composition assumptions, and the stringency of the regulatory standard. The model simulations showed reductions in urban background NO2 of 2.0 µg m −3, and at the scale of the greater Berlin area of 1.6 to 2.0 µg m −3 depending on the setup of the simulation and resolution of the model. Similar results were found for other European cities. The similarities in results using the measurement- and model-based methods support our ability to draw robust conclusions that are not dependent on the assumptions behind either methodology. The results show the significant potential for NO2 reductions if regulatory standards for light duty diesel vehicles were to be met under real-world operating conditions. Such reductions could help improve air quality by reducing NO2 exceedances in urban areas, but also have broader implications for improvements in human health and other benefits.